Pengaruh Peran Guru Dalam Proses Pembelajaran dan Intensitas Belajar Terhadap Hasil Belajar Siswa Kelas X IPS SMA Negeri 5 Padang Pada Mata Pelajaran Ekonomi Tahun Ajaran 2018/2019 - Nur Rizka Sari; Yulhendri Yulhendri (Universitas Negeri Padang, 2020)
This research aim to analyze: (1) the direct effect of the teacher's role in the learning process on student intensity of learning, (2) the direct effect of the teacher's role in the learning process on student learning outcomes, (3) the direct effect of student learning intensity on student learning outcomes, (4) the indirect effect of the teacher's role in the learning process on student learning outcomes through student learning intensity. This type of research is an associative descriptive study with the population is all students of class X IPS SMA Negeri 5 Padang Academic Year 2018/2019 and a sample of 121 people. The data analysis technique used is descriptive analysis, inferential analysis with path analysis. The results showed that (1) the role of the teacher in the learning process directly affected the intensity of student learning, (2) the role of the teacher in the learning process directly affected student learning outcomes, (3) the intensity of student learning directly affected student learning outcomes, and (4) there is an indirect effect of the teacher's role in the learning process on student learning outcomes through student learning intensity.Keywords: learning outcomes, the role of teacher, intensity of learning